The miRNA-608 rs4919510 G>C polymorphism confers reduce coronary injury of Kawasaki disease in a Southern Chinese population. Issue 5 (17th May 2019) - Wang, Yanfei; Lu, Zhaoliang; Fu, Lanyan; Tan, Yaqian; Che, Di; Huang, Ping; Pi, Lei; Xu, Yufen; Liang, Qihua; Zhang, Li; Qiu, Xiantao; Gu, Xiaoqiong
Abstract : Kawasaki disease (KD) is also called mucocutaneous lymph node syndrome and is an acute febrile pediatric disease characterized by systemic vasculitis. KD typically occurs in children 5 years old or younger and occurs more often in males than in females. miRNA-608 has been reported to interact with interleukin-6 and affect innate immunity. The immune-mediated inflammation could induce the occurrence of KD; however, there is no previous research focused on the relationship between miRNA-608 polymorphism and the KD risk. The present study explored the correlation between the miRNA-608 rs4919510 G>C polymorphism and the risk for KD. We recruited 532 patients with KD and 623 controls to genotype the miRNA-608 rs4919510 G>C polymorphism with a TaqMan allelic discrimination assay. Single-locus analysis showed no significant association between miRNA rs4919510 G>C polymorphism and KD susceptibility. However in an analysis stratified by age, gender, and coronary artery lesion (CAL), we found a relationship between the miRNA-608 rs4919510 G>C polymorphism and KD susceptibility. When KD patients were stratified by coronary injury, the CG/CC genotypes of the miRNA-608 rs4919510 G>C polymorphism contributed to a higher occurrence of KD than that was found in the GG genotype patients (adjusted odds ratio = 0.74, 95% CI = 0.56–0.98, P = 0.033). The present study demonstrated that the miRNA-608 rs4919510 G>C polymorphism may have a CAL-related relationship with KD susceptibility that has not been previously revealed.